37. INFANT DISEASE STRUCTURE AND RESPONSE ABILITY OF THACH THANH DISTRICT GENERAL HOSPITAL, THANH HOA PROVINCE PERIOD OF 2020-2022 (Vietnam Journal of Community Medicine, 2025)
General Hospital, Thanh Hoa province period of 2020-2022.Subjects and methods: The study used medical records of inpatients at Thach Thanh district General Hospital from 2020 to 2022. The study design was cross-sectional, combining quantitative and qualitative analysis (in-depth interviews).Results: During the period 2020-2022, respiratory diseases (Chapter X) accounted for the highest proportion (16.3%), followed by circulatory diseases (12.6%) and trauma and poisoning (12.7%). The group of non-communicable diseases accounted for the highest proportion (72.1%), followed by the group of accidents, poisoning and trauma (15.8%), while infectious diseases accounted for the lowest proportion (12.1%). Hospital bed occupancy rates ranged from 55.4% (2021) to 62.9% (2022), reflecting the impact of the COVID-19 pandemic on inpatient care.
Keywords: Disease structure; inpatient care; general hospital